2022
DOI: 10.1177/01945998221091697
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement Trends in Pediatric Otolaryngology From 2000 to 2020: A CMS Physician Fee Schedule Analysis

Abstract: Objective The aim of this study was to evaluate the financial trends in Medicare reimbursement rates for the most billed procedures at a single institution from 2000 to 2020 within pediatric otolaryngology. Study Design Retrospective data analysis. Setting United States. Methods The most billed surgical and in-office procedures in pediatric otolaryngology at our institution were identified in the Physician Fee Schedule Look-up Tool from the Centers for Medicare and Medicaid Services to extract reimbursement da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Inflation‐adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties 10,11,24 . This study found a 20.3% inflation‐adjusted decline in reimbursement of laryngeal procedures.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Inflation‐adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties 10,11,24 . This study found a 20.3% inflation‐adjusted decline in reimbursement of laryngeal procedures.…”
Section: Discussionmentioning
confidence: 58%
“…Inflation-adjusted declines in reimbursement have been found not only in neurosurgery, 4 general surgery, 5 orthopedic surgery, 6 reconstructive plastic surgery, 7 ophthalmology, 21,22 and interventional radiology 23 but also in otolaryngology 9 and its subspecialties. 10,11,24 This study found a 20.3% inflation-adjusted decline in reimbursement of laryngeal procedures. Though our study looked at a greater number of procedures within laryngology, this result is largely in line with the recent findings of Quereshy et al who found an inflation-adjusted decline of 19.4% among head and neck surgical oncology CPT codes 12 and Schartz et al who found an inflationadjusted decline of 21.2% among otology procedures.…”
Section: Discussionmentioning
confidence: 70%
“…These trends in reimbursement changes are consistent with other specialties and otolaryngology subspecialties. Within otolaryngology, common otolaryngology procedures performed in the facility setting saw a decrease of 37.63% in adjusted reimbursement from 2000 to 2019; otology procedures saw a decrease of 21.2% between 2000 and 2020; low‐wRVU rhinology procedures saw a decrease of 50% between 2000 and 2021; high wRVU rhinology procedures saw a decrease of 36.1% between 2000 and 2021; head and neck surgery procedures saw a decrease of 19% between 2000 and 2021; and pediatric otolaryngology procedures saw a decrease of 27.5% between 2000 and 2020 10–14 . Meanwhile, Medicare reimbursement for evaluation and management services has not decreased as much.…”
Section: Discussionmentioning
confidence: 99%
“…Within otolaryngology, common otolaryngology procedures performed in the facility setting saw a decrease of 37.63% in adjusted reimbursement from 2000 to 2019; otology procedures saw a decrease of 21.2% between 2000 and 2020; low-wRVU rhinology procedures saw a decrease of 50% between 2000 and 2021; high wRVU rhinology procedures saw a decrease of 36.1% between 2000 and 2021; head and neck surgery procedures saw a decrease of 19% between 2000 and 2021; and pediatric otolaryngology procedures saw a decrease of 27.5% between 2000 and 2020. [10][11][12][13][14] Meanwhile, Medicare reimbursement for evaluation and management services has not decreased as much. Between 2007 and 2022, 99204 (new outpatient visit, 45 min), 99213 (established outpatient visit, 15 min), 99214 (established outpatient visit, 25 min), 99222 (initial inpatient care, 50 min), and 99232 (subsequent inpatient care, 25 min) saw CAGRs of À0.8%, 1.1%, 0.6%, À1.5%, and À1.6%, and total percent changes of À10.4%, 15.8%, 7.6%, À18.2%, and À19.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rapoport et al found that computed tomography reliably revealed pre-epiglottic space invasion [32]. However, current imaging techniques do not consistently detect preepiglottic space invasion at the microscopic level [36][37][38]. More sensitive imaging methods and/or protocols incorporating the use of complementary approaches may improve the accuracy of preoperative predictions.…”
Section: Discussionmentioning
confidence: 99%